Analisis Variabel Yang Mempengaruhi Pemeliharaan Bangunan Gedung Berkelanjutan Dengan Metode Structural Equation Modeling - Widiastuti, Widiastuti; Sahadi, Sahadi; Poernomo, llham (Borneo Engineering: Jurnal Teknik Sipil, 2025)
Maintenance and care of buildings is absolutely necessary as an effort to extend the life of the building, so that the condition of the building is maintained properly. Over time, buildings experience a decrease in quality. However, this can be overcome by sustainable building maintenance. This research aims to determine the factors that influence sustainable building maintenance work, and determine the dominant factors that influence sustainable building maintenance work. The analysis method used is Structural Equation Modeling (SEM). Respondent was obtained through a questionaire with samples coming from stakeholders, work implementers and building users. The results of this study obtained seven variables that affect sustainable building maintenance, namely management and organization, human resources, building technical requirements, finance and budget, building users, laws and regulations, occupational safety and health. The most dominant variable is management and organization, with 52%.